The Influence of Grammatical Gender on the Sequence of Near-synonyms in Serbian Dictionaries in Contrast to English Thesauri - Čarapić, Dragana (Lexikos, 2022)
It has been noticed that Serbian dictionaries of synonyms do not provide a clear insight into the lexical relations among the words bearing similar meaning (PrÄ‡iÄ‡ 2010). Therefore, we have devised the multi-faceted approach to the research which incorporates the collocational, componential, and contrastive analysis of the descriptive adjectives hrabar, -a, -o, in Serbian, and its English counterpart brave. Specific emphasis has been given to the presence of grammatical gender (masculine, feminine, neuter) in Serbian in contrast to natural gender in English. Electronic databases and electronic corpora are used for the analysis of the most frequent collocational framework of the chosen samples. The results of the research employed illustrate how semantic (and grammatical) aspects of words are reflected onto and within their collocational range indicating idiomatic meaning of the adjectives analysed in both languages. Furthermore, the analysis applied has shown that the most frequent collocations of the adjective hrabar, -a, -o, have varied depending on the grammatical gender implied (masculine, feminine, neuter), as well as the sequence of its near-synonyms. The same changes have not occurred in English due to its lack of grammatical gender.Keywords: near-synonyms, descriptive adjectives, collocational analysis, componential analysis, contrastive analysis